Pre-repeat cooperative GBN-ARQ for TDD/TDMA based wireless networks - Luo-bing DONG; Ke-chu YI; Pei-yi SHEN; Quan YU (Tongxin xuebao)
An efficient pre-repeat cooperative go-back-N automatic repeat request(PC-GBN-CARQ)algorithm for slow fading TDD/TDMA-based Wireless Networks was proposed.Taking advantage of the multiple access property of TDMA,the proposed scheme enabled both the source and the relay to retransmit packets to the destination simultaneously,which could greatly increase the successful probability of the retransmission.When the source was sending a group of data packets,it also sent 8bit of attached message to tell the relay about which packets among the group would be probably error in transmission,which was the result predicted based on TDD reciprocity,so that the relay could also pre-retransmit these packets like the source does.It should be very effective to raise the transmission efficiency.Simulation results show that the proposed algorithms can get an S/N ratio gain of about 5dB compared with the conventional ones for the normalized throughput of 0.7.